Handbook for supply chain risk management : case studies, effective practices, and emerging trends - Khan, Omera, 1976-; Zsidisin, George A. (J. Ross Pub., 2012)
Failure to manage supply chain risk effectively can have a significant negative impact on an organization. Over 30 international contributing authors provide a set of best practices, processes, tools and techniques, supported by cases and illustrative examples, that can be adopted to proactively evaluate, manage, or mitigate risk in their supply chains and improve overall business performance.